To check to make sure what you're talking about, you have

x^7 / (2x^4 +5)^1/3 dx ?

If so, start by substituting

x^4 for u

x^4 = u

4x^3dx = du

dx = du/4x^3

Substitute back in. We're only going to substitute dx at first

x^7/ (2x^4 +5)^1/3 * du/4x^3

Note that the x^7/4x^3 will reduce to x^4/4, which allows us to substitute it for u.

1/4 (integral ( u/(2u +5)^1/3 du)) = 1/4 * 3/40 (2u +5)^(2/3) * (4u -15)

Substitute u back in and we arrive at

1/4 * 3/40 * (2x^4 +5)^(2/3) * (4x^4 -15)

Hope that helped. -Edit-